(untitled) (Journal of Parents and Teachers, 2025)
The article refers to two questions and the answers provided by people knowledgeable about the topic. First, it discusses whether one should have a home library, offering children an opportunity to spark their curiosity for reading. Secondly, it addresses the question of whether children should play chess from a young age.